2019
DOI: 10.1093/cercor/bhz084
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Speech Motor Control Revealed with Time-Resolved fMRI

Abstract: Holding a conversation means that speech must be started, maintained, and stopped continuously. The brain networks that underlie these aspects of speech motor control remain poorly understood. Here we collected functional magnetic resonance imaging (fMRI) data while participants produced normal and fast rate speech in response to sequences of visually presented objects. We took a non-conventional approach to fMRI data analysis that allowed us to study speech motor behavior as it unfolded over time. To this end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…First, it is worth pointing out the diversity of temporal profiles that underlie the production of speech. For example, for all ICs there is strong synchronized activity across trials, but for some this synchronized activity is of a rather short duration (IC5, 8,9), for others this synchronized activity has a longer duration (IC6, 10,11). Similarly, for some regions activity has a sharp rising edge while for others there is a more gradual slope (cf., IC5 and IC6).…”
Section: Icmentioning
confidence: 99%
See 2 more Smart Citations
“…First, it is worth pointing out the diversity of temporal profiles that underlie the production of speech. For example, for all ICs there is strong synchronized activity across trials, but for some this synchronized activity is of a rather short duration (IC5, 8,9), for others this synchronized activity has a longer duration (IC6, 10,11). Similarly, for some regions activity has a sharp rising edge while for others there is a more gradual slope (cf., IC5 and IC6).…”
Section: Icmentioning
confidence: 99%
“…The anatomical sources and their temporal dynamics observed in the current study correspond closely to those reported in previous studies. Previous hemodynamic studies of picture naming have typically reported activity in medial and lateral regions of the occipital cortex, in medial inferior and middle gyri of the temporal cortex, in posterior medial and inferior lateral portions of the parietal cortex, and in medial anterior (cingulate) and in medial and lateral (motor) regions of the frontal cortex 8,[10][11][12]57,58 . The current study found activations in occipital (cuneus, lateral, fusiform), temporal (inferior, middle), frontal (medial cingulate, lateral), and parietal areas (inferior, superior) and thus align with those previously reported.…”
Section: Icmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we relied on the spatially restricted group ICA technique (srICA; Blessing et al 2016;Ezama et al 2021;Formisano et al 2004). Whole-brain ICA is frequently used to separate signal from noise in fMRI studies (e.g., Janssen and Mendieta 2020;Smith et al 2013). Instead, by applying ICA to a particular brain region, the noise profile that is specific to that brain region will be taken into account and result in a more sensitive separation of signal from noise in that region.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Xu et al (2014) developed a more sophisticated dual‐masked s‐ICA technique to denoise TCM in an overt‐language fMRI paradigm collected on healthy young participants. In the realm of routine bulkhead motion correction, Janssen and Mendieta (2020)) employed the standard ICA‐based denoising package (i.e., AROMA) to correct for motion in an overt picture naming task collected on healthy young subjects, while (Sebastian et al, 2016) utilized a rigid body alignment approach (i.e., MCFLIRT) to correct for motion in an overt picture naming task collected from acute stroke patients. However, given that speech related motion is not just spatially selective, but also temporally correlated with task‐induced hemodynamic response, and can vary from epoch to epoch (Gopinath et al, 2009), optimization of TCM denoising approaches to account for the noise jointly encoded in both spatial and temporal domains is equally important.…”
Section: Introductionmentioning
confidence: 99%